Modified hydrodissection to prevent intraoperative iris prolapse. Issue 12 (December 2020) - Huynh, Michelle L.; Sanders, Riley; Sallam, Ahmed B.
Abstract : A modified hydrodissection technique to prevent intraoperative iris prolapse is presented. The phacoemulsification tip is inserted into the main ocular incision while hydrodissection is performed through a side-port incision. Placement of the phacoemulsification tip in this location prevents iris prolapse. This technique can be used routinely and might be especially applicable in cases with a high risk for iris prolapse, such as in intraoperative floppy-iris syndrome.